GC-MS ANALYSIS AND PHYTOCHEMICAL SCREENING OF A FERN HEMIONITIS ARIFOLIA (BURM.) MOORE FROM TIRUMALA HILLS - K. RUKMINI; P.SUVARNALATHA DEVI; CH. M. KUMARI CHITTURI (International Journal of Pharma and Bio Sciences, 2015)
The present paper reveals the phytochemical screening and GC-MS analysis of Hemionitis arifolia. Phytochemical studies showed the presence of alkaloids, flavonoids, phenols, tannins and saponins in higher to moderate concentrations and percentage of alkaloid 0.28 %, flavonoid 0.32 %, tannins 0.26% and saponins 0.52%. Butanol extract of the plant was analysed using Gas Chromatography- Mass Spectrometry, while the mass spectra of the compounds found in the extract was matched with the National institute of standards and technologies (NIST) library. Gas chromatography mass spectrometry (GC-MS) analysis revealed the presence of six compounds. The phytoconstituents screened were Mesityl oxide, 2- pentanone, Benzene, Neophytadiene, 2- Hexadecen-1,ol, n-Hexadecanoic acid, Phytol, oleic acid, stearic acid, Stigmast-4-en-3-one. The ten compounds were identified by comparing their retention time and peak area with that of literature and by interpretation of mass spectra. This study scientifically validates the use of plant and further research leading to possible drug development.